Exploring knowledge-building in tour guiding research: A content analysis of empirical papers on tour guiding, 1980–2015. (December 2018) - Chen, Hanyu; Weiler, Betty; Black, Rosemary
Abstract: Despite tour guides being substantial influencers in the tourism industry, tour guiding research is relatively recent and receives insufficient scholarly attention. This paper provides a content analysis of empirical English-language journal articles on tour guides and tour guiding covering a 36-year-period. Papers were coded by journal discipline, authorship, location of study and methodology. Key findings show that while tour guiding is receiving increasing attention from researchers, research is somewhat unevenly spread geographically. Knowledge-building of tour guiding could benefit from a wider range of study locations, investigations of additional guide genres, a greater use of mixed methods and, most importantly, collaboration across locations and genres.